Digitalization of public administration as a main principle at the fighting corruption in the Republic of Kazakhstan - Kuanaliyev, A.A. (BUKETOV BUSINESS REVIEW, 2021)
Object: Digitalization itself and as a result of digitalization of public administration is a globally actual trend. Especially after last pandemic year when government staff mostly had to work remotely. This may be one of the reason of Kazakhstan’s improvement at the corruption ranking. The purpose of this study is to determine the relationship between the level of digitalization of public administration and the level of perception of corruption. Methods: Methods of grouping and classification, as well as methods of mathematical modeling were used in processing and systematization of data. Findings: While looking over history of corruption and digitalization it was revealed that countries with high level of digitalization of public administration have good positions at the corruption perceptions index (CPI). Before starting the study, the author put forward a logical hypothesis about the presence of a high directly proportional relationship between these two characteristics, to confirm which mathematical analysis (Cramer’s rule) was applied. A brief overview of the development of corruption and digitalization starting from the first moments of the beginning of both phenomena was given. Conclusions: As a result of the study, a correlation with the R2 coefficient equal to 0.8988 was found, which confirmed the accepted hypothesis. In other words, a high level of digitalization of public administration makes it possible to improve indicators in the corruption perception index.